Pengaruh Variasi Produk dan Kepercayaan Pelanggan terhadap Loyalitas Pelanggan Melalui Variabel Intervening Keputusan Pembelian di Grup Order pada Album K-Pop: Studi Kasus pada Fanbase SEVENTEEN - Anna Wijayanti; Hadita Hadita; Neng Siti Komariah; Dewi Puspaningtyas Faeni; Yayan Hendayana (International Forum of Researchers and Lecturers, 2024)
This research aims to find out whether purchasing decisions can influence product variety and customer trust in customer loyalty to SEVENTEEN's K-Pop album. The method used in this research is quantitative. The sample used was 100 respondents and focused only on the SEVENTEEN fanbase. The sampling technique uses Purposive Sampling technique. The data collection technique uses a questionnaire. The data analysis technique uses the SmartPLS 4.0 software statistical method. The results of this research show that there are variables that influence each other, as in the following brief explanation: 1). Product variations do not have a positive and significant effect on purchasing decisions, 2). Customer Trust has a positive and significant effect on Purchasing Decisions, 3). Product variety has a positive and significant effect on customer loyalty, 4). Customer Trust has a positive and significant effect on Customer Loyalty, 5). Purchasing Decisions have a positive and significant effect on Customer Loyalty, 6). Purchasing Decisions are not able to fully mediate Product Variations on Customer Loyalty, 7). Purchasing Decisions are able to fully mediate Customer Trust towards Customer Loyalty.